The Philosophical Mea Culpa of the Icons of the Death of the Author - Krasniqi, Nysret (Problemos, 2019)
[full article, abstract in English; abstract in Lithuanian]We will hereinafter discuss the author’s philosophy on gnoseological and historical premises. More precisely, by exploring the genealogy of the idea of the “Death of the Author” from modernism to postmodernism, we will analyse the concepts and ideologies that have become the stratagem of the denial of western literary canon, as well as the denial of equilibrium between philosophical and literary identity and universality. By treating the works of philosophers, authors, and fundamental semiologists who perpetuated the idea of the Death of the Author, we will observe how the latter gradually fled from the philosophy of doubt and as mea culpa admitted that without the author’s authority the philosophical and literary legacy is no longer the theatre of memory, but the abyss of oblivion. Moreover, with fundamental examples, we will observe the influence of this philosophy in the process of studying of the literature.
Keywords: philosophy of literature; the Death of the Author; classic literature; identity; teaching of literature